IMPACT OF DIMETHOATE ON PROTEIN CONTENT IN THE FRESHWATER FISH PUNTIUS TICTO (HAM) - R. M. GANESHWADE,; R. M. GANESHWADE,; P. B. ROKADE,; S. R. SONWANE, (The Bioscan, 2011)
Puntius ticto, a freshwater fish exposed to lethal (5.012 ppm) and two sublethal concentrations of dimethoate (2.506 ppm and 1.253 ppm) for 96h and 60 days and protein content was observed from different tissues after the exposure period. Acute exposure (5.012 ppm) results in significant decrease in the level of protein in testis, ovary and brain and slight decrease in intestine, muscles, liver and gills; whereas increased protein level was observed in kidney. Chronic toxicity results showed decrease in the level of protein content in ovary, brain, intestine, muscles, gills and liver to 2.506 and 1.253 ppm exposure; whereas in testis protein level was increased to 1.253 ppm and decrease protein content was observed in 2.506 ppm exposure.